Screening for PTSD during pregnancy: a missed opportunity - Avelina C. Padin; Natalie R. Stevens; Mandy L. Che; Ihuoma N. Erondu; Marisa J. Perera; Madeleine U. Shalowitz (BMC, 2022)
Abstract Background Prenatal posttraumatic stress disorder (PTSD) is often overlooked in obstetric care, despite evidence that untreated PTSD negatively impacts both mother and baby. OB-GYN clinics commonly screen for depression in pregnant patients; however, prenatal PTSD screening is rare. Although the lack of PTSD screening likely leaves a significant portion of pregnant patients with unaddressed mental health needs, the size of this care gap has not been previously investigated. Methods This retrospective chart review study included data from 1,402 adult, pregnant patients who completed PTSD (PTSD Checklist-2; PCL) and depression (Edinburgh Postnatal Depression Survey; EPDS) screenings during a routine prenatal care visit. Descriptive statistics identified screening rates for PTSD and depression, and logistic regression analyses identified demographic variables associated with screening outcomes and assessed whether screening results (+ PCL/ + EPDS, + PCL/-EPDS, -PCL/ + EPDS, -PCL/-EPDS) were associated with different provider intervention recommendations. Results 11.1% of participants screened positive for PTSD alone, 3.8% for depression alone, and 5.4% for both depression and PTSD. Black (OR = 2.24, 95% CI [1.41,3.54]) and Latinx (OR = 1.64, 95% CI [1.01,2.66]) patients were more likely to screen positive for PTSD compared to White patients, while those on public insurance were 1.64 times (95% CI [1.21,2.22]) more likely to screen positive compared to those with private insurance. Patients who screened positive for both depression and PTSD were most likely to receive referrals for behavioral health services (44.6%), followed by -PCL/ + EPDS (32.6%), + PCL/-EPDS (10.5%), and -PCL/-EPDS (3.6%). A similar pattern emerged for psychotropic medication prescriptions. Conclusions Over ten percent of pregnant patients in the current study screened positive for PTSD without depression, highlighting a critical mental health need left unaddressed by current obstetric standards of care. Routine PTSD screening during prenatal care alongside strategies aimed at increasing referral resources and access to mental health services are recommended.